Focus on Apple Aperture - Hilz, Corey (Focus on series (Focal Press), 2011)
Are you into photography not photomanipulation?Frustrated that you are spending too much time in front of the screen and not enough behind the lens?Feel like you are not getting the most out of the powerful processing functions of Apple Aperture? This straightforward, inspiring guide is aimed at photographers whose goal is to use the software to bring out the best in their photographs. Professional photographer and educator Corey Hilz leads you through a highly effective, professional's workflow with Aperture, from importing your photos from your camera and.